Evaluation of fecal microbiomes associated with obesity in captive cynomolgus monkeys (Macaca fascicularis) - Koo, Bon-Sang (J Vet Sci, 2019)
Microorganisms play important roles in obesity; however, the role of the gut microbiomes in obesity is controversial because of the inconsistent findings. This study investigated the gut microbiome communities in obese and lean groups of captive healthy cynomolgus monkeys reared under strict identical environmental conditions, including their diet. No significant differences in the relative abundance of Firmicutes, Bacteroidetes and Prevotella were observed between the obese and lean groups, but a significant difference in Spirochetes (p < 0.05) was noted. Microbial diversity and richness were similar, but highly variable results in microbial composition, diversity, and richness were observed in individuals, irrespective of their state of obesity. Distinct clustering between the groups was not observed by principal coordinate analysis using an unweighted pair group method. Higher sharedness values (95.81% ± 2.28% at the genus level, and 79.54% ± 5.88% at the species level) were identified among individual monkeys. This paper reports the association between the gut microbiome and obesity in captive non-human primate models reared under controlled environments. The relative proportion of Firmicutes and Bacteroidetes as well as the microbial diversity known to affect obesity were similar in the obese and lean groups of monkeys reared under identical conditions. Therefore, obesity-associated microbial changes reported previously appear to be associated directly with environmental factors, particularly diet, rather than obesity.